Acanthoic acid modulates lipogenesis in nonalcoholic fatty liver disease via FXR/LXRs-dependent manner. (25th September 2019) - Han, Xin; Cui, Zhen-Yu; Song, Jian; Piao, Hui-Qing; Lian, Li-Hua; Hou, Li-Shuang; Wang, Ge; Zheng, Shuang; Dong, Xiu-Xiu; Nan, Ji-Xing; Wu, Yan-Ling
Abstract: Acanthoic acid (AA) is a pimaradiene diterpene isolated from Acanthopanax koreanum Nakai (Araliaceae), with anti-inflammatory and hepatic-protective effects. The present study intended to reveal the effect and mechanism of AA on nonalcoholic fatty liver disease (NAFLD) associated with lipid accumulation by activating Farnesoid X receptor (FXR) and liver X receptors (LXRs) signaling. C57BL/6 mice were received a modified Lieber-DeCarli diet with 71% high-fat (L-D) and treated with AA (20 and 40 mg/kg) or equal volume of saline for 12 weeks. The regulation of AA on lipid accumulation was also detected in pro-steatotic stimulated AML12 cells with palmitic acid (PA). When L-D diet-fed mice were treated with AA, loss in body weight, liver index, and liver lipid droplet were observed along with reduced triglyceride (TG) and serum transaminase. Furthermore, AA decreased sterol regulatory element binding protein 1 (SREBP-1) and target genes expression, regulated PPARα and PPARγ expressions, ameliorated hepatic fibrosis markers, enhanced hepatic FXR and LXR, and regulated AMPK-LKB1 and SIRT1 signaling pathway. Moreover, AA attenuated lipid accumulation via FXR and LXR activation in steatotic AML-12 cells, which was confirmed by guggulsterones (FXR antagonist) or GW3965 (LXR agonist). Activation of FXR and LXR signaling caused by AA might increase AMPK-SIRT1 signaling and then contribute to modulating lipid accumulation and fatty acid synthesis, which suggested that activated FXR-LXR axis by AA represented an effective strategy for relieving NAFLD. Graphical abstract: Image 1 Highlights: Acanthoic acid eliminates lipogenesis in NAFLD via FXR-LXRs activation. Acanthoic acid decreases lipid accumulation in differentiated 3T3-L1 adipocytes. Acanthoic acid attenuates hepatosteatosis via FXR-LXRs activation in AML-12 cells.